Produksi Bahan Bakar dari Limbah Plastik HDPE dan LDPE Menggunakan Metode Pirolisis - Enggar Hero Istoto; Pipit Puspitasari (Syntax Corporation Indonesia, 2024)
The purpose of this study is to calculate the volume and composition of fuel produced from the production of fuel from polyethylene plastic waste per liter. Method: research using pyrolysis method with temperature 450-621°C without using catalyst, and quantitative analysis. Quantitative analysis using the GC-MS method. Result: Pyrolysis of 5 Kg HDPE waste produces 3.25 liters of naphtha, 0.85 liters of gasoline; diesel 0.325 liters; and activated carbon 18.06 grams. 5 Kg LDPE waste produces 500 mL naphtha, 2.9 liters of gasoline; diesel 0.1 liters; and 19 grams of activated carbon. Conclusion: Pyrolysis of 5 Kg HDPE waste produces 3.25 liters of naphtha; gasoline 0.85 liters; diesel 0.325 liters (88.86% total fuel), and activated carbon 18.06 grams; and 5 Kg LDPE waste produces 2.9 liters of gasoline; 0.1 liters of diesel (70.38% of total fuel), and 19 grams of activated carbon. The composition of fuel produced in pyrolysis of polyethylene plastic waste (HDPE and LDPE) in the form of naphtha, gasoline, and diesel and produces residues in the form of activated carbon.